War brides: a practice-based examination of translating women’s voices into textile art - Beccue-Barnes, Wendy Davis (Kansas State University, 2012)
Research about military wives has been limited. In academia, most research centers on the soldier and/or the family as a unit. When literature does address only the wife’s perspective it rarely presents a positive portrayal of her life. However, it is not just literature that shows a gap in exposing the voice of the military wife. Art-based works rarely focus on her perspective; and methodologies, such as practice-based research, rarely utilize actual voices as inspiration. The aim of the current study was to discover the voice of the military wife, examine it through a feminist lens, and then translate those voices into artwork that represented the collective, lived experience of the women interviewed. Three methodologies were utilized to analyze and translate the voices of military wives into textile art. These three methodologies: practice-based research, phenomenology, and feminist inquiry provided a suitable structure for shaping the study to fulfill the project aim. Interviews conducted with 22 military wives revealed two overarching themes: militarization and marriage; as well as multiple subthemes. Three subthemes were recognized as being the most prominent: relationships, separation, and collective experience. These themes were used as the inspiration for the creation and installation of three textile art pieces. The current study serves to fill the gaps in both the literature and the artistic process by presenting both the positive and negative aspects of the military wife’s lived experience and using that lived experience as inspiration for textile art.
Keywords: Military wives; Practice-based research; Textile art; Design research; Qualitative methods; Feminist inquiry; Design (0389); Military Studies (0750); Women's Studies (0453)